2006
DOI: 10.1128/jb.188.3.1134-1142.2006
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Gene Transfer and the Evolution of Microvirid Coliphage Genomes

Abstract: Bacteriophage genomic evolution has been largely characterized by rampant, promiscuous horizontal gene transfer involving both homologous and nonhomologous source DNA. This pattern has emerged through study of the tailed double-stranded DNA (dsDNA) phages and is based upon a sparse sampling of the enormous diversity of these phages. The single-stranded DNA phages of the family Microviridae, including X174, appear to evolve through qualitatively different mechanisms, possibly as result of their strictly lytic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
143
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(152 citation statements)
references
References 51 publications
(46 reference statements)
6
143
0
1
Order By: Relevance
“…For the ssDNA phage fX174, which is a close relative of our wild-type phage ID11 (Rokyta et al 2006b), Vale et al (2012) found that, for 36 random mutations, fitness effects …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the ssDNA phage fX174, which is a close relative of our wild-type phage ID11 (Rokyta et al 2006b), Vale et al (2012) found that, for 36 random mutations, fitness effects …”
Section: Resultsmentioning
confidence: 99%
“…In the present work, we attempted to shift the wild-type genotype, ID11, and its nine previously described beneficial mutations (Rokyta et al 2005(Rokyta et al , 2008(Rokyta et al , 2011 closer to and farther from the optimal phenotype by changing the temperature at which fitness was measured, to quantify the changes in fitness effects and patterns of epistatic interactions between mutations. Previous work has shown that close relatives of ID11 in the G4-like group of microvirid coliphages (Rokyta et al 2006b) tend to have fitnesses inversely correlated with temperature (Knies et al 2009). The original mutations were isolated by means of selection at 37°, and we therefore attempted to move the genotypes closer to the optimum by measuring fitnesses at a lower temperature (33°) and farther from the optimum by measuring fitnesses at a higher temperature (41°), leaving the genotypes involved constant.…”
mentioning
confidence: 99%
“…Members of the Microviridae infecting a diverse range of hosts (including proteobacteria, Spiroplasma, Chlamydia) have been isolated and completely sequenced (Sanger et al, 1977;Renaudin et al, 1987;Storey et al, 1989;Lui et al, 2000;Read et al, 2000;Brentlinger et al, 2002;Garner et al, 2004;Rokyta et al, 2006). Genome comparisons have identified two distinct groups of Microviridae (those similar to the chlamydiaphages and those similar to Escherichia coli fX174), leading to the suggestion that ssDNA phages evolve through different mechanisms than dsDNA phages (Brentlinger et al, 2002;Rokyta et al, 2006). Although the Microviridae have been extensively studied, the sequenced representatives infect a small number of bacterial hosts.…”
Section: Resultsmentioning
confidence: 99%
“…Research was conducted using the bacteriophage ID11, a member of family Microviridae described by Rokyta et al (2006b). ID11 is a single-stranded DNA icosahedral virus with a genome 5577 bases long encoding 11 genes.…”
Section: Strainsmentioning
confidence: 99%